Peningkatan Efisiensi dan Akurasi Kehadiran Sekolah: Sistem Berbasis IoT dengan Teknologi RFID di SMK Putra Anda Binjai - Arpan; Mohammad Yusup; Aidil Ahmad (Universitas Sari Mutiara Indonesia Medan, 2024)
Efficient and accurate school attendance is paramount for the seamless operation of educational institutions. This research focuses on enhancing attendance systems by implementing an Internet of Things (IoT)-based solution with Radio-Frequency Identification (RFID) technology at SMK Putra Anda Binjai. The study employs an experimental design, dividing students and teachers into control and experimental groups. The control group retains the conventional attendance system, while the experimental group adopts the IoT-based RFID technology. The research encompasses careful sample selection, integrating hardware and software tools, and automated data collection procedures. Findings highlight the system's benefits, such as improved efficiency, real-time monitoring, and enhanced accuracy. Challenges, including initial implementation hurdles and technical glitches, are also identified. A comparison with conventional systems underscores the superiority of the IoT-based RFID technology, showcasing higher accuracy and time efficiency. The positive impact on the academic atmosphere aligns with literature emphasizing technology's role in advancing learning environments. This research signifies a transformative initiative in school attendance, offering insights into the potential of technologically advanced educational settings. Continuous refinement is essential for maximizing benefits and addressing real-world educational challenges.